PERANCANGAN APLIKASI BERBASIS WEB DAN ANDROID UNTUK PENJUALAN DAN PEMBELIAN PADA APOTEK CANON - Havana Havana (Jurnal Ilmu Komputer dan Sistem Informasi, 2018)
Web and android based program for the sale of and the purchase by an apothecary is application made as to make it easier for an apothecary operational canon. The application of sales and the purchase by a canon of apothecary this is intended to help the proprietors in civil servants and manage the sales and the purchase by an apothecary of a canon , of employees will be manage the sales and the purchase of through the application of web and the owners will manage through android mobile .Application designed by using a programming language asp.net and android, in addition there are forecasting features stock uses the method linear regression simple .A method of the design of application using system development life cycle by using the method waterfall. The results of testing carried out using a method of user acceptance test and testing user satisfaction on the use of questionnaires .With the existence of this application can ease civil servants and the proprietors in the selling process and the purchase by an apothecary of a canon.